Biosynthesis, characterization, and antimicrobial applications of silver nanoparticles - Singh P (Dove Medical Press, 2015)
Priyanka Singh,1 Yeon Ju Kim,2 Hina Singh,1 Chao Wang,2 Kyu Hyon Hwang,3 Mohamed El-Agamy Farh,1 Deok Chun Yang1,2 1Department of Oriental Medicinal Material and Processing, 2Graduate School of Biotechnology and Ginseng Bank, College of Life Sciences, Kyung Hee University, Yongin, 3Gyeonggi-Do Agricultural Research & Extension Services, Gyeonggi, Republic of Korea Abstract: In the present study, the strain Brevibacterium frigoritolerans DC2 was explored for the efficient and extracellular synthesis of silver nanoparticles. These biosynthesized silver nanoparticles were characterized by ultraviolet-visible spectrophotometry, which detected the formation of silver nanoparticles in the reaction mixture and showed a maximum absorbance at 420 nm. In addition, field emission transmission electron microscopy revealed the spherical shape of the nanoparticles. The dynamic light scattering results indicated the average particle size of the product was 97 nm with a 0.191 polydispersity index. Furthermore, the product was analyzed by energy dispersive X-ray spectroscopy, X-ray diffraction, and elemental mapping, which displayed the presence of elemental silver in the product. Moreover, on a medical platform, the product was checked against pathogenic microorganisms including Vibrio parahaemolyticus, Salmonella enterica, Bacillus anthracis, Bacillus cereus, Escherichia coli, and Candida albicans. The nanoparticles demonstrated antimicrobial activity against all of these pathogenic microorganisms. Additionally, the silver nanoparticles were evaluated for their combined effects with the commercial antibiotics lincomycin, oleandomycin, vancomycin, novobiocin, penicillin G, and rifampicin against these pathogenic microorganisms. These results indicated that the combination of antibiotics with biosynthesized silver nanoparticles enhanced the antimicrobial effects of antibiotics. Therefore, the current study is a demonstration of an efficient biological synthesis of silver nanoparticles by B. frigoritolerans DC2 and its effect on the enhancement of the antmicrobial efficacy of well-known commercial antibiotics. Keywords: Brevibacterium frigoritolerans, biosynthesis, silver nanoparticles, antimicrobial activity, synergistic effect